2018
DOI: 10.1590/1806-9282.64.02.187
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic steatohepatitis in posttransplantation liver: Review article

Abstract: Introduction: Nonalcoholic steatohepatitis (NASH) associated or not with cirrhosis is the third leading indication for liver transplantation (LT) around the world. After transplants, NASH has a high prevalence and occurs as both recurrent and de novo manifestations. De novo NASH can also occur in allografts of patients transplanted for non-NASH liver disease. Objective: To evaluate recurrent or de novo NASH in post-LT patients. Method: A literature review was performed using search engines of indexed scientifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 64 publications
0
12
0
1
Order By: Relevance
“…No significant difference in 5-year graft loss or mortality was observed, suggesting that NASH itself is not an independent risk factor for mortality. In a meta-analysis of 16 studies on post-LT survival with NASH, most studies found no significant survival difference was found between NASH and other etiologies of liver disease[ 149 ]. Another study documented superior survival in NASH patients compared with LT recipients for other causes for transplantation, such as HCC, hepatitis C or alcoholic liver disease[ 150 ].…”
Section: Outcomes For Lt In Nash Recipientsmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant difference in 5-year graft loss or mortality was observed, suggesting that NASH itself is not an independent risk factor for mortality. In a meta-analysis of 16 studies on post-LT survival with NASH, most studies found no significant survival difference was found between NASH and other etiologies of liver disease[ 149 ]. Another study documented superior survival in NASH patients compared with LT recipients for other causes for transplantation, such as HCC, hepatitis C or alcoholic liver disease[ 150 ].…”
Section: Outcomes For Lt In Nash Recipientsmentioning
confidence: 99%
“…Despite lack of non-inferior survival data, the overall incidence of morbidity after LT appears to be higher for NASH recipients than others[ 156 ]. Metabolic syndrome develops in up to 50% of patients after LT for NASH; however, no significant difference between NASH and other etiologies of liver disease has been shown[ 149 ]. Nonetheless, it is postulated that LT recipients with NASH have a predisposing metabolic milieu that persists despite transplantation, and it may be further modulated by steroid-based immunosuppressive regimens.…”
Section: Outcomes For Lt In Nash Recipientsmentioning
confidence: 99%
“…117,118 NAFLD recurrence after liver transplantation is a vexing problem, and its incidence has been reported to be anywhere between 15 and 100%. 119 Post-transplant metabolic syndrome has multifactorial etiologies, although adverse effect profile of immunosuppressive agents (steroids, calcineurin inhibitors, mTOR inhibitors, and so on) and lack of adherence to lifestyle modifications are its major contributors. Physicians ought to educate their patients on the pivotal role of diet and exercise after liver transplantation and attempt risk factor modification (e.g., control of high blood pressure, diabetes, dyslipidemia, obesity, CKD) with appropriate counseling and pharmacotherapy.…”
Section: Liver Transplant In Patients With Nafldmentioning
confidence: 99%
“…NAFLD is divided into two major subtypes: nonalcoholic fatty liver (NAFL also called simple steatosis), which is a form of nonprogressive NAFLD that rarely develops into cirrhosis, and nonalcoholic steatohepatitis (NASH), a progressive and aggressive form of NAFLD. Long-term NASH is highly likely to progress to cirrhosis and hepatocellular carcinoma (HCC) [1]. NASH is considered an intermediate stage of liver damage and the most extreme form of NAFLD [2].…”
Section: Introductionmentioning
confidence: 99%
“…1 Spectrum of NAFLD progression. The development of NAFLD is divided into four stages: simple steatosis (or NAFL), NASH, liver cirrhosis, and eventually HCC [1]. Factors that cause simple steatosis include Western HFHSDs, obesity, T2DM (particularly the associated IR), and other metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%